SERVICE PROVISION FOR CEREBRAL VENOUS SINUS THROMBOSIS. A UK SURVEY. Issue 12 (15th November 2016) - Lavin, Tim; Punter, Martin; Holland, Mark
Abstract : Introduction: Cerebral Venous Sinus Thrombosis (CVST) is a rare but serious cause of disability and death. No guidance on CVST service design exists. We sought to establish how CVST is cared for across the UK. An online survey was distributed to members of the Association of British Neurologists, British Association of Stroke Physicians and the Society of Acute Medicine. There were 194 respondents. Results: Most respondents reported that their units saw fewer than 10 cases/year (72.9%). These cases were cared for on a Neurology (41.8%) or Stroke unit (38.4%), but 15.7% were cared for on non-specialist wards. Respondents reported a majority of patients have a Neurologist or a Stroke Physician, as their named consultant (38.4% and 36% respectively) yet fewer would see a Neurologist or Stroke Physician within 24 hr (55.2%). Over half (59.3%) reported their units always sought a specialist opinion within 24 hr, and reported that the opinion sought was a Neurologist (75.6%). Conclusion: Provision of care for patients with CVST is mainly through specialist services and is evenly split between acute stroke and neurology. Most cases are cared for by a neurologist or stroke physician, but just over half would see a specialist within 24 hours of admission.